2013
DOI: 10.1016/j.dcm.2013.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Reversing racism and the elite conspiracy: Strategies used by the British National Party leader in response to hostile media appearances

Abstract: This paper addresses the talk of the leader of the British National Party leader, Nick Griffin, when he spoke on the BBC following a surge in electoral success for the party. Inclusion in these programmes demonstrated political progress for the BNP, yet ironically facilitated breadth of criticism for the party, as his appearances were met with widespread hostility and accusations of extremism. Reactive rhetoric to these criticisms is central to Griffin rebranding the party and becoming part of mainstream UK po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Billig () showed how this cultural norm is so widespread that it is drawn upon and referred to (or to use the DP term ‘oriented to’) by those who may be most expected to be accused of being prejudiced: in his study, ‘new racists’, people purportedly with ‘authoritarian’ personalities (see Adorno, Frenkel‐Brunswick, Levison, & Stanford, ), anti‐immigration MPs, right wing politicians and fascists. In my own research (Johnson & Goodman, ), it has been shown how the leader of the British far‐right party the British National Party (BNP) suggests that there is racism in the UK but that it is not organisations such as the BNP that are racist, and instead, it is a white majority in the country who are the ‘real’ victims of racism. This provides a more recent example of someone who may be (and often is) accused of racism, drawing on the taboo against prejudice, rather than rejecting it; all is in the service of denying prejudice and forwarding arguably prejudicial ideals.…”
Section: Discursive Psychology (Dp) and The Norm Against Prejudicementioning
confidence: 99%
“…Billig () showed how this cultural norm is so widespread that it is drawn upon and referred to (or to use the DP term ‘oriented to’) by those who may be most expected to be accused of being prejudiced: in his study, ‘new racists’, people purportedly with ‘authoritarian’ personalities (see Adorno, Frenkel‐Brunswick, Levison, & Stanford, ), anti‐immigration MPs, right wing politicians and fascists. In my own research (Johnson & Goodman, ), it has been shown how the leader of the British far‐right party the British National Party (BNP) suggests that there is racism in the UK but that it is not organisations such as the BNP that are racist, and instead, it is a white majority in the country who are the ‘real’ victims of racism. This provides a more recent example of someone who may be (and often is) accused of racism, drawing on the taboo against prejudice, rather than rejecting it; all is in the service of denying prejudice and forwarding arguably prejudicial ideals.…”
Section: Discursive Psychology (Dp) and The Norm Against Prejudicementioning
confidence: 99%
“…Taken together, these posts collaboratively construct the decision as causing problems for the UK and these problems are attributed to British MPs who do not care about the British public, which mirrors the talk of the far-right British National Party (BNP) about immigration (Johnson & Goodman, 2013). The rhetorical question that completes the post supports both previous ideas (i) that the decision is unpopular and (ii) that politicians are not representing the will of the wider public.…”
Section: Positioning the Decision To Allow In Child Refugees As Opposmentioning
confidence: 62%
“…As well as the clearly anti-immigrant rhetoric, even applied to children orphaned through war, there is also the conspiratorial argument that states that the government (and indeed all politicians) are so out of touch that they work against the interests of the general population in supporting immigration, so that existing citizens are being discriminated against. This argument was used by Nick Griffin, then leader of the far-right BNP, in his anti-immigration and anti-EU comments (Johnson & Goodman, 2013) and this is also apparent in some of the posts featured here (particularly "Mike" in extract 14). While the BNP are not referred to in the discussion, instead UKIP and its leader Nigel Farage are presented as the solution to the problem by those in the debate, which suggests that what was considered to be the talk of an extremist has now become commonplace, with popular support, at least in this particular discussion.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…28, 36;Matthews and Brown, 2012). While the coverage of both Jean-Marie Le Pen and Nick Griffin was hostile, this offered the leaders of parties whose platform had been marginalised the opportunity to stand as the outsiders, vocal opponents of the establishment -in contrast to other alternatives given little or no coverage (Akkerman, 2011;Johnson and Goodman, 2013). This in turn paved the way for a more amenable reception of leaders whose persona and discourse appeared more moderate.…”
Section: Crises Pnps and The Media Effect: A Perfect Storm?mentioning
confidence: 99%